Bell pepper (Capsicum annuum) response to self-regulating low energy clay-based irrigation (SLECI) system, burying depth and fertilizer application dosage - Gilbert Osei; Joshua Owusu-Sekyere; Livingstone Sam-Amoah; Francis Kumi; Harald Hansmann; Vincent Agyemang; Ransford Darko; Kezia Mensah; Delwyn Okhumai (Journal of Central European Agriculture)
The response of bell pepper (Capsicum annuum) to the Self-regulating low energy clay-based irrigation (SLECI) system burying depth and fertilizer application dosage was investigated under open field conditions in the coastal savannah agroecological zone of Ghana. A factorial design with 3 SLECI system depths (5 cm, 10 cm and 15 cm) and 3 fertilizer dosages (100% recommended application dosage RAD, 80% RAD and 60% RAD) was adopted. Data was measured, determined and analyzed at a significant (P ≤ 0.05) level. Results indicated that the highest yield of 0.7974 t/ha was recorded under a burying depth of 5 cm which is 8.6% and 63.9% more compared to 10 cm and 15 cm. Burying depth of 10 cm exhibited the highest water use efficiency of 0.1435 kg/l, which outperformed the 5 cm burying depth (0.1312 kg/l) and 15 cm burying depth (0.0517 kg/l) by 8.6% and 63.9%, similarly a depth of 10 cm (5,980 kg/kg) exhibited significantly greater fertilizer use efficiency over a depth of 15 cm (2,154 kg/kg) by 64% and 5 cm by (5.465 kg/kg). The highest yield of 0.8772 t/ha was exhibited by 80% RAD which is 29.5% and 63.7% more compared to 100% RAD (0.6179 t/ha) and 60% RAD (0.3181 t/ha) respectively. 80% RAD exhibited significantly superior water use efficiency of 0.1579 kg/l, and fertilizer use efficiency of 6,579 kg/kg. The interaction of burying depth of 10 cm and 80% RAD significantly produced the highest yield of 1,187.7 t/ha, resulted in the highest water use efficiency of 0.214 kg/l, and exhibited the best-performing fertilizer use efficiency of 8,908 kg/kg.